The evolution of stagecraft at Eurovision Song Contest (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
Since its inception in 1956, Eurovision Song Contest has evolved from minimalist stages to hybrid and technologically experiences, integrating light, space, and multimedia. Innovations such as LED screens, mapping, augmented reality and kinetic elements transform audience’s perception. Influences from Appia, Craig, Svoboda, Wilson and Lepage demonstrate the transition toward the “total artwork.” Additionally, Turrell and Eliasson’s proposals enrich the expanded scenography, exploring light as a material and multisensory participation. Each edition acts as a scenographic laboratory, where the physical and digital converge, redefining the aesthetic experience and establishing the festival as a benchmark of technological and visual innovation in large-scale events.
Keywords: Eurovision; scenography; technology; history; innovation